2016
DOI: 10.1021/acs.est.6b02913
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Life Cycle Analysis of Water and CO2-Based Fracturing Fluids Used in Unconventional Gas Production

Abstract: Many of the environmental impacts associated with hydraulic fracturing of unconventional gas wells are tied to the large volumes of water that such operations require. Efforts to develop nonaqueous alternatives have focused on carbon dioxide as a tunable working fluid even though the full environmental and production impacts of a switch away from water have yet to be quantified. Here we report on a life cycle analysis of using either water or CO for gas production in the Marcellus shale. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…A modified version of the PLUMED 2.3.0 plugin was used to apply the bias forces to maintain the fluid composition in the control regions. 69 The target CO 2 and CH 4 densities in the control regions were set to two CO 2 and two CH 4 molecules/ nm 3 . At the simulated temperature of 323 K, the reference target densities of fluid species in the control regions correspond to a total fluid pressure of 124 bar, based on the Peng−Robinson equation of state.…”
Section: Methodsmentioning
confidence: 99%
“…A modified version of the PLUMED 2.3.0 plugin was used to apply the bias forces to maintain the fluid composition in the control regions. 69 The target CO 2 and CH 4 densities in the control regions were set to two CO 2 and two CH 4 molecules/ nm 3 . At the simulated temperature of 323 K, the reference target densities of fluid species in the control regions correspond to a total fluid pressure of 124 bar, based on the Peng−Robinson equation of state.…”
Section: Methodsmentioning
confidence: 99%
“…Sustainability 2018, 10, 164 2 of 23 economic research of considering the potential application of SG [7,25,[33][34][35][36], the environmental impact assessment in SG exploitation [21,[37][38][39][40][41][42][43][44][45][46][47][48] and many others. Anyway, with the evolution from initial exploitation to the more and more complicated development of SG, the diverse research of SG can be found in available literature during past decades.…”
Section: Methodsmentioning
confidence: 99%
“…SG has complex characteristics such as large reserves, long production cycle, somewhat expensive exploration costs compared with other unconventional types of gas reservoirs and so on. The complexity of SG brings that the fields of SGR during the past years are diverse, which include theoretical SGR of analyzing the foundation of SG exploration [1,2,10,[24][25][26], model investigation in SG [24,[27][28][29][30][31][32][33], technical and economic research of considering the potential application of SG [7,25,[33][34][35][36], the environmental impact assessment in SG exploitation [21,[37][38][39][40][41][42][43][44][45][46][47][48] and many others. Anyway, with the evolution from initial exploitation to the more and more complicated development of SG, the diverse research of SG can be found in available literature during past decades.…”
Section: Introductionmentioning
confidence: 99%
“…• Flow of acidic brine through fractures in mineralogically heterogeneous rocks selectively dissolves calcite and creates a porous layer • Calcite-depleted porous layer collapses under normal stresses, filling the fracture with fine particles, decreasing permeability • Layer of fine particles lowers fracture frictional strength because it prevents the formation of interlocking microasperities 2013; Fang et al, 2016;Majer et al, 2007;Moeck et al, 2009;Rinaldi et al, 2015;Segall & Fitzgerald, 1998;Talwani, 1997;Walsh & Zoback, 2016;Zoback & Gorelick, 2012). Concurrently, the injection of fluids into the subsurface can create reactive fluids, such as the injection of CO 2 which dissolves in water and forms carbonic acid (Benson & Cole, 2008;Bielicki et al, 2018;Borgia et al, 2012;Gaus, 2010;Pearce & Dawson, 2018;Wilkins et al, 2016). Such reactive brines can enter and alter flow pathways by dissolving reactive minerals and increasing fracture permeability (e.g., Hawkes et al, 2005).…”
Section: 1029/2019jb017805mentioning
confidence: 99%